Поняття «повсякденність» у пострадянській історіографії - Леснича, Пауліна Станіславівна; Lesnycha, Paulina S. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Проаналізовано різні підходи до проблеми дефініції поняття «повсякденність» у пострадянській істо-ріографії. Зроблено спробу виокремити основні риси щодо його змістового наповнення в теоретико-методо-логічному доробку українських, російських та білоруських учених. The research is devoted to the problem of analysis different approaches to the concept «the everyday life» and to the issue of the subject of study of the everyday life history, a new area of historical scolarship. The article gives an analysis of basic theoretical and methodological researches of Ukrainian, Russian and Belarusian scientists. It was attempted to summarize these approaches to the subject of study of the concept «the everyday life». The basic concept of all these research is the way of life. The main groups were determined by author given the degree of emphasis on household or / and on mental and emotional state of person and society in the daily life.
The Concept «the Everyday Life» in Postsoviet Historiography
Keywords: пострадянська історіографія; поняття «повсякденність»; історія повсякденності; методологія дослідження; the concept «the everyday life»; the research methodology, postsoviet historiography; the everyday life history